Stable Price Dispersion - David P. Myatt; David Ronayne (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2025)
We study the pricing of homogeneous products sold to customers who consider different sets of suppliers. We seek prices that are stable in the sense that no firm wishes to undercut any rival or to raise its price when rivals have a subsequent opportunity to undercut it. We identify stable and dispersed prices that emerge from both collective choice and non-cooperative pricing games, and derive predictions for prices across several price-consideration specifications. We show how the implications for firms and customers compare to those generated by conventional approaches.
Keywords: 330